1995
DOI: 10.1097/00005392-199502000-00055
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Low Energy Lithotripsy With the Lithostar

Abstract: Between November 1988 and July 1993, 238 renal stones and 208 ureteral stones were treated in 446 pediatric patients using 26 mobile and 2 fixed base Siemens Lithostar lithotriptors. The stones were treated by a group of 245 urologists using the modified Puigvert technique and the standard shock tube. The success rate for renal stones (asymptomatic fragments less than 4 mm.) was 76.6%, stone-free rate was 67.9%, retreatment rate was 14.1% and ancillary procedures were performed in 36.3%. The stone-free rate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
16

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 24 publications
4
21
0
16
Order By: Relevance
“…In general, both methods are safe and effective. Despite the minimally invasive nature of in situ ESWL, stone-free success rates vary and multiple treatments are required to achieve a stone-free outcome [24,25]. Furthermore, in situ ESWL is known to be less effective for stones of > 10 mm, impacted stones, radiolucent stones, and for cystine and calcium oxalate monohydrate stones [26][27][28][29].…”
Section: Fig 1 Ab Ivu From a 9-year-old Child With Bilateral Lowementioning
confidence: 99%
“…In general, both methods are safe and effective. Despite the minimally invasive nature of in situ ESWL, stone-free success rates vary and multiple treatments are required to achieve a stone-free outcome [24,25]. Furthermore, in situ ESWL is known to be less effective for stones of > 10 mm, impacted stones, radiolucent stones, and for cystine and calcium oxalate monohydrate stones [26][27][28][29].…”
Section: Fig 1 Ab Ivu From a 9-year-old Child With Bilateral Lowementioning
confidence: 99%
“…Estudos têm demonstrado que a litotripsia extracorpórea causa lesões no parênquima renal, relacionadas ao número de impulsos e à intensidade das ondas de choque 10 . Lesões permanentes no parênquima renal, entretanto, não têm sido demonstradas 10 .…”
Section: Introductionunclassified
“…SWL has been the treatment of choice for renal calculi less than 15 mm in size. The stone-free rates range from 68 to 84% [1]. In our study, ESWL was found to be safe and eVective in children as was in adults for solitary renal and upper ureteric stones less than 2 cm in size.…”
mentioning
confidence: 51%